2007
DOI: 10.1002/app.26907
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the decay of methyl cellulose‐manganate(VI) polysaccharide transient species–novel spectrophotometric kinetic trace of methyl cellulose hypomangate(V) gel intermediate polysaccharide

Abstract: Kinetics of the decay of methyl cellulosemanganate(VI) intermediate polysaccharide 22 ] have been followed spectrophotometrically in different strong basic solutions at different temperatures, as well as, in the presence of different concentrations of perchlorate salt. The reaction is base-catalyzed. Salt never affects the reactivity. The activation parameters have been evaluated and discussed in connection with the proposal mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
1
19
1
Order By: Relevance
“…The experimental results in the present redox reaction indicated that the oxidation kinetics was complex in nature. It has been reported that the alcoholic polysaccharides possess high affinity for deprotonation in alkaline solutions to give the more reactive alkoxides prior to the rate‐determining step as follows: () PS n+OH(PS)n+normalH2Owhere PS represents the alcoholic polysaccharides and PS − is the corresponding alkoxide formed. If such deprotonation occurs in the present work, the oxidation process should have been occurred between two negative charge anions as reactive species, hexacyanoferrate(III) and the formed alkoxide, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results in the present redox reaction indicated that the oxidation kinetics was complex in nature. It has been reported that the alcoholic polysaccharides possess high affinity for deprotonation in alkaline solutions to give the more reactive alkoxides prior to the rate‐determining step as follows: () PS n+OH(PS)n+normalH2Owhere PS represents the alcoholic polysaccharides and PS − is the corresponding alkoxide formed. If such deprotonation occurs in the present work, the oxidation process should have been occurred between two negative charge anions as reactive species, hexacyanoferrate(III) and the formed alkoxide, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results in the present redox reaction indicated that the oxidation kinetics was complex in nature. It has been reported that the alcoholic polysaccharides possess high affinity for deprotonation in alkaline solutions 22,23,[42][43][44][45] to T A B L E 3 The activation parameters of the second-order rate constant (k n ) in the oxidation of pectin along with that for oxidation of other polysaccharides by alkaline hexacyanoferrate(III) give the more reactive alkoxides prior to the rate-determining step as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, permanganate ion is a strong oxidizing agent which has been widely used for oxidation of most organic and inorganic compounds (Stewart, 1965;Lee, 1980;Fatiadi, 1987;Dash, Patel, & Mishra, 2009), a little attention has been focused to the oxidation of macromolecules by this oxidant. Eventhough, the kinetics of permanganate oxidation of some carbohydrates containing secondary alcoholic groups such as alginates (Hassan, 1993), pectates (Khairou & Hassan, 2000;Khairou, 2003;Abdel-Mohsen & Nassr, 2010), carboxymethyl cellulose (Shaker, 2001) and methyl cellulose (El-Khatib, 2002;Shaker, El-Khatib, & Mahran, 2007) in alkaline solution has been studied by us for the first time. Unfortunately, the oxidation of sulfated carbohydrates has received a little attention .…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above aspects in addition to our interest in the oxidation kinetics of carbohydrates by either this oxidant (Hassan, 1993;Khairou & Hassan, 2000;Khairou, 2003;Abdel-Mohsen & Nassr, 2010;Shaker, 2001;Shaker, El-Khatib, & Mahran, 2007;El-Khatib, 2002; or by other oxidants Zaafarany et al, 2009;, the present work seems to be of great importance with the aims at shedding more highlights on the nature of the formed intermediates in terms of electron-transfer processes and the transition states in the rate-determining step as well as to compare the results obtained with that previously reported for oxidation of other sulfated carbohydrates by this oxidant in alkaline solutions in an attempt to elucidate a suitable reaction mechanism for oxidation in these redox systems. In addition, this work aims to synthesize a novel coordination biopolymer chelating agent.…”
Section: Introductionmentioning
confidence: 99%